Comparative In vitro Evaluation of Widely Used Aquaculture Disinfectants Against Major Marine Bacterial Fish Pathogens - T. G. Sumithra; S. Aparna; Andria; N. S. Ashily; V. N. Anusree; P. K. Patil; S. R. Krupesha Sharma (Journal of Fish Diseases, 2026)
Effective disinfection is a critical component of aquaculture biosecurity. The present study evaluated in vitro efficacy of eight commonly used disinfectants [Chloramine‐T, benzalkonium chloride (BKC), iodophor, formalin, sodium hypochlorite, hydrogen peroxide (H 2 O 2 ), potassium permanganate (KMnO4), and glutaraldehyde] against three major marine pathogens, viz. Streptococcus agalactiae , Photobacterium damselae , and Vibrio vulnificus . Multiple evaluations were performed, including determination of minimum inhibitory concentration (MIC), time‐kill kinetics, effective concentration, influence of organic load, and an integrated activity scoring system. Sodium hypochlorite and BKC had the maximum and minimum MICs, respectively, across all three species. The least coefficient of variation % in MIC across different species was shown by BKC (34.4%). Iodophor and Chloramine‐T achieved a ≥ 5 log 10 reduction in all pathogens within 10 min at their MIC level. Formalin could not achieve the desired results even at 16‐fold higher MIC values, showing its unsuitability for rapid surface disinfection protocols. All disinfectants showed reduced efficacy even at an organic load level of 0.5%. Integrated scoring system graded iodophor and BKC as the most effective disinfectants (> 80% of total score), making them strong candidates for aquaculture disinfection programmes. Collectively, the findings serve as the reference for adopting effective biosecurity practises against bacterial pathogens in marine/estuarine aquaculture.

Insights on recent baleen whale (Cetacea: Mysticeti) stranding events along the south-west coast of India - R. Ratheesh Kumar; T.G. Sumithra; U. Utthamapandian; V. Durga; S. Monolisha; Alvin Anto; S. Vinayak; K.V. Akhilesh; Grinson George; A. Gopalakrishnan (Regional Studies in Marine Science, 2025)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Heritability, genetic advance and marker-trait associations through bulked segregant analysis for bacterial leaf blight resistance in Rice in F2:3 population of TRY 3 x IRBB60 - V. Sumithra; M. Arumugam Pillai (South African Journal of Botany, 2025)

Characterization of novel L-asparaginases having clinically safe profiles from bacteria inhabiting the hemolymph of the crab, Scylla serrata (Forskål, 1775) - V. P. Lailaja; T. G. Sumithra; K. J. Reshma; V. N. Anusree; P. V. Amala; T. G. Kishor; N. K. Sanil (Folia Microbiologica, 2022)

Antibody-based biosensor to detect oncogenic splicing factor Sam68 for the diagnosis of lung cancer - B. Sumithra; V. S. P. K. Sankara Aditya Jayanthi; Hari Chandana Manne; Rashmika Gunda; Urmila Saxena; Asim Bikas Das (Biotechnology Letters, 2020)

Evaluation of Oxidative Stress and hsCRP in Polycystic Ovarian Syndrome in a Tertiary Care Hospital - N. Unni C. Sumithra; R. Lakshman Lakshmi; N. Leela Menon; K. N. Subhakumari; V. S. Sheejamol (Indian Journal of Clinical Biochemistry, 2015)

Multiplex Polymerase Chain Reaction Assay for the Specific Detection of the Organism Causing Anthrax - T. G. Sumithra; V. K. Chaturvedi; P. K. Gupta; S. C. Sunita; S. J. Siju; C. Susan; J. Vergis (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Mycoplasmosis in wildlife: a review - T. G. Sumithra; V. K. Chaturvedi; C. Susan; S. J. Siju; A. K. Rai; C. Harish; S. C. Sunita (European Journal of Wildlife Research, 2013)